Relationship between the electric field integral value and vacuum breakdown characteristics in small electrode with multi‐apertures. Issue 11 (3rd October 2019) - Okura, Tetsuya; Nishiyama, Masashi; Yamano, Yasushi; Kojima, Atsushi; Kashiwagi, Mieko
Abstract : For a critical plasma test equipment JT‐60SA, vacuum electric breakdown around apertures is a serious problem for developing a high‐energy and high‐power negative ion source accelerator. To improve the high voltage performance of the accelerator, we investigated the relation of a breakdown electric field in a vacuum with the electric field integral value of electrode's surface for multi‐apertures electrode. The results of breakdown tests for various types of multi‐aperture electrode show that the electric field integration ES had a relation with the vacuum breakdown field and field emission current characteristics. The reduction in the ES with the relaxation of electric fields improved the breakdown performance. Moreover, the low value of ES decreased the field enhancement factor ' β ' and the emission area ' A ' of field electron emission from the electrode. Therefore, we found that the breakdown electric field can be improved by reducing the prebreakdown current that flows before the occurrence of breakdown by reducing the ES . © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.